Synthesis and Characterization of Binary Reduced Graphene Oxide/Metal Oxide Nanocomposites - Avar, Baris; Panigrahi, Mrutyunjay (Physics and Chemistry of Solid State, 2022)
Graphene/metal oxide composites have generated interest for a variety of applications, such as energy storage, catalysts, and electronics, etc. However, one of the primary technical barriers to real applications has been the lack of practical and environmentally benign synthesis methods for producing homogenous graphene/metal oxide nanocomposites on a wide scale. Therefore, a simple, efficient, and environmentally friendly approach to the synthesis of graphene (reduced graphene oxide: rGO)/metal oxide (MO) nanocomposites was developed with the chemical reaction of graphene oxide (GO) and various metal oxide powders under mild temperature conditions. In this study, the GO was synthesized from graphite powder using modified Hummer’s technique initially. Later, using ascorbic acid (AA) as a reducing agent, various binary nanocomposites such as rGO/ZnO, rGO/CuO, rGO/TiO2, and rGO/Ag2O were synthesized by in situ approach. The structural and surface properties of the synthesized binary nanocomposites were extensively examined by X-ray diffraction (XRD), Field emission scanning electron microscopy (FESEM), Energy dispersive spectroscopy (EDX), and Raman spectroscopy techniques. The XRD analysis of the synthesized binary rGO/MO nanocomposites confirmed the nanocrystalline nature. However, the FESEM and EDX analysis substantiated the MO nanoparticles were uniformly distributed onto the rGO layers anchoring of MO onto rGO particles and interacted with the rGO residual functional groups. Raman spectroscopy analysis indicated the increased number of defects because of the interfacial interaction between rGO and MO and the formation of binary rGO/MO nanocomposites.